Evaluasi Rencana Tata Ruang Wilayah Kota Pangkalpinang Tahun 2011-2030 Berdasarkan Sebaran Kerawanan Banjir - Fitriansyah, Hadi; Ajrina, Fadiah Izzah; Caesar, Muhammad Yusuf; Maulidya, Haya Aqilah (LPPM ITK, 2024)
Flooding occurs when river water overflows and inundates the surrounding flat areas due to the river's inability to contain excess water. Pangkalpinang City, as the capital of Bangka Belitung Islands Province, has several locations that are prone to flooding during the rainy season. There have been 192 flood incidents across seven districts, making it crucial for decision-makers to identify flood-prone areas for planning purposes and to better understand the vulnerable regions to implement more effective preventive measures. This study aims to map the distribution of flood-prone areas and analyze the correlation between the spatial plan of Pangkalpinang City for 2011-2030 and flood-prone regions. The study uses scoring, weighting, and overlay methods with ArcMap 10.8 software. The data used in this study include slope gradient, elevation, soil type, land use, and rainfall. It is important to evaluate the Spatial Plan of Pangkalpinang City for 2011-2030 concerning flood vulnerability. The results of the study show that flood hazard classes in Pangkalpinang City are dominated by the low hazard class covering an area of 910.74 ha, the moderate hazard class covering 5,959.63 ha, and the high hazard class covering 3,559.90 ha. The benefits of evaluating the spatial plan of Pangkalpinang City based on flood vulnerability distribution include raising awareness among the government and the public regarding flood disasters, enabling the city government to utilize the results to strengthen flood mitigation efforts, improving the effectiveness of planning and environmental management, and optimizing land use. The spatial plan based on flood-prone areas shows that the protected area, covering 1,274.98 ha, predominantly falls into the high flood-prone category, while the cultivation area, covering 5,275.52 ha, predominantly falls into the moderate flood-prone category.